Management of osteoporosis in men based Ukrainian version of FRAX - Povoroznyuk, Vladyslav; Grygorieva, Nataliia; Musiienko, Anna; Bystrytska, Maryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective. The aim of the study was to evaluate the impact of the previous published FRAX thresholds in a male referral cohort from Ukraine. Methods. The cohort comprised 653 men aged 40‒88 years (mean age 60.5 ± 11.8). The 10-year probabilities of hip fracture and a major osteoporotic fracture were calculated using the Ukrainian FRAX model. The intervention threshold was set at the age specific fracture probability as first used by the National Osteoporosis Guideline Group for FRAXbased guidelines in the UK and adapted for the Ukraine. Treatment pathways were compared with a previously published female referral cohort from Ukraine. Results. 27 % of men and 51 % of women referred for skeletal assessment had a prior fracture that categorized eligibility for treatment that was more frequent in women than in men. The requirement for BMD testing was also higher in women than in men (18.3 % vs. 4.9 %, respectively). If referral for fracture risk assessment was contingent on the presence of at least one FRAX risk, the proportion of men and women eligible for treatment would rise from 5 % to 89 % in men and from 57 % to 93 % in women. Conclusions. This study demonstrated a higher need for both antiosteoporotic treatment without DХA and additional densitometric examination to further assess the osteoporotic fractures risk in Ukrainian women compared to men and the need for special attention in fracture risk assessment in men with previous fractures. The development of National guidelines together with a validation based on cost-effectiveness would help drive a cohesive national approach to risk assessment in both men and women.